2006
DOI: 10.1682/jrrd.2004.09.0118
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Perceived Deficits Questionnaire of Multiple Sclerosis Quality of Life Inventory with Beck Depression Inventory and neuropsychological tests

Abstract: Abstract-The Perceived Deficits Questionnaire (PDQ) is a part of the Multiple Sclerosis (MS) Quality of Life Inventory that assesses self-perceived cognitive difficulties. We used baseline data from 49 MS subjects participating in a clinical trial to evaluate the correlation of the PDQ with two measures of cognitive impairment, the Paced Auditory Serial Addition Test (PASAT) and the California Verbal Learning Test, 2nd edition (CVLT-II), total score, and one measure of depression, the Beck Depression Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 23 publications
11
41
0
1
Order By: Relevance
“…Nonetheless, the remainder of null findings confirm the weak association between subjective and objective cognitive performance previously described in the literature. 12,14,15,22 In contrast, reports of cognitive concerns on the PDQ were highly correlated with concomitant reports of depression, anxiety, fatigue, and self-efficacy, in line with existing literature. 15,19,21 Among these variables, reports on the PDQ were most highly correlated with vegetative symptoms of depression (r = 0.60 to 0.66) addition, each index of the PDQ (ie, Attention, Memory, and Planning) maintained significant associations with each self-report factor.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Nonetheless, the remainder of null findings confirm the weak association between subjective and objective cognitive performance previously described in the literature. 12,14,15,22 In contrast, reports of cognitive concerns on the PDQ were highly correlated with concomitant reports of depression, anxiety, fatigue, and self-efficacy, in line with existing literature. 15,19,21 Among these variables, reports on the PDQ were most highly correlated with vegetative symptoms of depression (r = 0.60 to 0.66) addition, each index of the PDQ (ie, Attention, Memory, and Planning) maintained significant associations with each self-report factor.…”
Section: Resultssupporting
confidence: 84%
“…As with the MSNQ, previous investigators have been unable to find a direct and consistent relationship between this measure and objective neuropsychological test performance. 14,15 Reports on the PDQ have similarly been found to be related to concomitant reports of depression. 15 Moreover, in a recent study examining the PDQ in a population of patients with lupus, who tend to underreport cognitive concerns, Vogel et al 16 observed a high correlation between subjective cognitive concerns as measured by the PDQ and self-rated depressive symptoms.…”
mentioning
confidence: 99%
“…The significant relation of the CIS patients' MSNQ scores to some of the psychosocial measures is in line with previous findings in MS cohorts [12,13,14,15,22]. Similarly, the lack of significant correlations between the CIS patients' MSNQ scores and their performance on objective cognitive tests is also in line with previous findings in MS.…”
Section: Discussionsupporting
confidence: 90%
“…It is well established that in MS, patient self-report of cognitive problems is generally influenced by depression and less related to the patient's performance on objective tests of cognitive function [11,12,13,14]. Depression, anxiety, fatigue and disability, but not objective test performance, have been significantly linked to self-reported cognitive impairment [15].…”
Section: Introductionmentioning
confidence: 99%
“…Gleichzeitig existieren in einigen Studien Hinweise auf einen Zusammenhang zwischen der häufig beschriebenen chronischen Müdigkeit bei an MSErkrankten und der Entwicklung affektiver Begleiterkrankungen (Chwastiak et al 2005;MacAllister et al 2005). Als weiterer Hinweis auf Depressivität im Rahmen von Multipler Sklerose könnte auch das subjektive Erleben von kognitiver Einschränkung in Betracht gezogen werden, das die durch neuropsychologische Testung objektivierbaren Defizite häufig übertrifft (Lovera et al 2006;Deloire et al 2006). Beide Hypothesen bestätigen sich am Beispiel unseres Patienten, dessen Konzentrations-und Merkfähigkeitsstö-rungen, von ihm als sehr quälend erlebt, nur teilweise im Rahmen einer neuropsychologischen Testung objektiviert werden konnten.…”
Section: Multipler Sklerose Und Psychiatrische Komorbiditätunclassified